STUDENTS’ ERRORS IN TRANSLATING MATHEMATICAL REPRESENTATIONS FROM SYMBOLIC TO GRAPHICAL FORM IN QUADRATIC FUNCTIONS - Safitri, Rizqi Febriana; Qohar, Abd.; Sisworo, Sisworo (AKSIOMA: Jurnal Program Studi Pendidikan Matematika, 2025)
Representation is an important element in mathematics learning that helps make abstract mathematical ideas more concrete. Changes between forms of representation, called translations of mathematical representations, are necessary in mathematics learning. However, students often struggle with this process, as evidenced by errors in problem-solving. These errors can be categorized into three types: interpretation errors, implementation errors, and preservation errors. Based on these facts, a solution is needed to overcome student errors. However, to formulate the right solution, an in-depth study is needed regarding student errors in translation. Therefore, this study aims to analyze and describe junior high school students' errors, especially in translating representations from symbolic to graphical form in quadratic function material. The method used is descriptive qualitative, involving three class IX students with different mathematical abilities as research subjects. The results of this study showed that high-ability students made few interpretation, implementation, and preservation errors from the stage of unpacking the source to constructing the target. Moderate-ability students made some interpretation and implementation errors from the stage of unpacking the source to constructing the target. Meanwhile, low-ability students made many interpretation, implementation, and preservation errors from the stage of unpacking the source to determining equivalence. To overcome these errors, teachers can apply level 1 scaffolding (environmental provisions) and level 2 scaffolding (explaining, reviewing, and restructuring). In conclusion, students with different mathematical abilities each have difficulties in making translations. The factors causing these errors include inaccuracy, neglect of important aspects, inappropriate habits, and conceptual errors.